The 4 routes to entrepreneurial success - iner, John B M. (Berrett-Koehler, 1996)
The book provides four personality types characterize successful entrepreneur - Personal achievers, Supersalespeople, Real managers, and Expert idea generators. The routes by which each type achieves success are explored in detail, and numerous real-life examples of established entrepreneurs are included throughout